PELANGGARAN PRINSIP KERJA SAMA PERCAKAPAN DALAM ACARA MATA NAJWA DI METRO TV - Afif Setiawan; Rokhmat Basuki; Ngudining Rahayu (Universitas Bengkulu, 2017)
The purpose of this study is to describe the form of violations of the principle of cooperation of conversation in the event of Mata Najwa on Metro TV. The method used in this research is descriptive qualitative method. The data source in this research is Najwa Shihab speech and its speaker in Mata Najwa on Metro TV. The data in this study were three episodes of Mata Najwa events in June, August, and December namely: the episode of